The Relative Demise of the Concept of Representation in Contemporary Sociology. Durkheim's, Parsons', Giddens' Models - Valantiejus, Algimantas (Sociologija. Mintis ir veiksmas, 2002)
This article critically examines the notion of representation by specifying the critical aspects of its contemporary development. The concept of “representation” most forcefully advanced by Durkheim has formed the basis for a kind of the social science that stresses the “naturalistica objectivity and externality of so called social facts. The unique and external character of what Durkheim terms reality sui generis is equivalent of Parsons' concem with what he called the “emergent properties” of social systems. The turn of latter-day sociological inquiry shows that under the new perspective the sociology undergoes a radical reframing of “representationalism”. As the self-sufficient social facts or the reality sui generis is treated with distrust, the emphasis is laid upon contextual, pragmatic aspects of an academic activity. The relationship between text and reality is reformulated and Challenges the representationalist paradigm prevalent in sociology. Furthermore, the narrative approach forces us to explore our understanding of the moral origins of sociological theory.
Keywords: representation; sociology; modernism; Emile Durkheim; Talcott Parsons; Anthony Giddens